PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, PENDAPATAN DI LUAR GAJI, DAN KEPUASAN KERJA TERHADAP MOTIVASI PEGAWAI BALAI METROLOGI JAWA TENGAH - Mr. Haryono; Yayat Hidayat Amir (Multiplier: Jurnal Magister Manajemen, 2017)
The aims of this research is to know the influence of independent variables (leadership, organization culture, and income out of salary) to dependent variables (job satisfaction and motivation). This research is doing using quantitative approach. Data of this research are response from 5 Likert Scale. On the income out of salary provide the opened questioners. Population on this research are employees on Meteorological Agency of Central Java consist of 6 Meteorological Agency that are Semarang area, Pati area, Tegal area, Banyumas area, Surakarta area, and Magelang area. Population consist of 160 employees on Meteorological Agency of Central Java take 114 sample by random technique and the proportion of 6 Meteorological Agency in Central Java area with refer to sampling technique of Slavin formula. This way done so that employees in Meteorological Agency in each territory can have the same chance to be a respondent. Therefore, all of proportional samples based on the number of employees in Meteorological Agency of each territory. Data analysis using regression technique to know the beta coefficient of regression as the method of calculating the analysis. Result of the research, 1) leadership doesn’t significantly influence to motivation, and have indirect influence to motivation through job satisfaction; 2) organization culture doesn’t significantly influence to motivation; and have significant to motivation indirectly through satisfaction work; 3) income out of salary significantly influence to motivation either directly or indirectly; 4) job satisfaction significantly influence to the motivation; 5) leadership significantly influence to job satisfaction; 6) organization culture significantly influence to the job satisfaction; and 7) income out of salary significantly influence to job satisfaction. Suggestion for this research are: 1) to headmaster of meteorological agency of Central Java must implemented the leadership style and forming the organization culture which oriented on job motivation; not only oriented on job satisfaction; and 2) to the next researcher must doing the research using qualitative about the leadership, organization culture, job satisfaction factors, and motivation factors of employees in Meteorological Agency of Central Java. Keywords: leadership, organization culture, income out of salary, job satisfaction, and motivation.